If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(9-t)=0
We add all the numbers together, and all the variables
-4(-1t+9)=0
We multiply parentheses
4t-36=0
We move all terms containing t to the left, all other terms to the right
4t=36
t=36/4
t=9
| 2(3a+4)=17 | | 8(3x+9)=6x+252 | | 25m+700=6700 | | x²+10x+20=0 | | 6x+2x+34=58 | | -5/9=x/18 | | b/7=2.5 | | -7(n+2)=-14-14n | | 11r-r-r-3=15 | | 98x+451=36x+1195 | | 10+2=4(7x-3) | | 28x=-35 | | -2x-4-3x=-10 | | 5(x+6)=4x+2x-10 | | 4(1-x)x3x=2(x-1) | | 0.5m—3.5=3m+6.5 | | 3q-7=17 | | -b-(13=4b)=-3(5-9b)+2 | | x+2.9=6.3 | | 6+x=-7+2x | | 28+7x=49+7x | | -17(y+3)+6(4y-3)=6(y-3)+14 | | 1x=11.75 | | 83=5(7-a)-a | | 3x+3-6=-9 | | x/2+17=17 | | 2x-2=-2x=12 | | 5f+9=12f-26 | | -3z-9=-42 | | -4x+6/7=2 | | 3x2-26x+32=0 | | 18x+x=205 |